2018
DOI: 10.1186/s41155-018-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with common mental disorders among female nursing professionals in primary health care

Abstract: Objective: To analyze the factors associated with common mental disorders (CMD) in primary care female nursing professionals. Methods: We performed exploratory cross-sectional study, using a structured questionnaire, applied to 451 primary care female nursing professionals from five municipalities of Bahia, Brazil, in a randomly selected sample. The outcome variable (CMD) was evaluated by SRQ-20. To analyze the factors associated with the prevalence of CMD, logistic regression analysis was used in blocks. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 48 publications
(60 reference statements)
4
14
0
4
Order By: Relevance
“…In this regard, Riecher-Rössler (2020) stated that in spite of important evidence that shows differences in mental disorders by sex and gender, there is still little real comprehension of these differences’ causes [ 39 ]. One explanation for the greater QoL impact among women during the pandemic could be the heavy load of self-assumed or socially imposed home responsibilities, even among women professionals [ 40 ]. Recently, in Chile, it was reported that female teachers experienced significant work exhaustion and lower engagement compared to their male work peers, regardless of whether there were children in their home, results that can be complemented with other pre-pandemic studies in Chile, which reported that working-age women had a higher probability of suffering stress than men [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Riecher-Rössler (2020) stated that in spite of important evidence that shows differences in mental disorders by sex and gender, there is still little real comprehension of these differences’ causes [ 39 ]. One explanation for the greater QoL impact among women during the pandemic could be the heavy load of self-assumed or socially imposed home responsibilities, even among women professionals [ 40 ]. Recently, in Chile, it was reported that female teachers experienced significant work exhaustion and lower engagement compared to their male work peers, regardless of whether there were children in their home, results that can be complemented with other pre-pandemic studies in Chile, which reported that working-age women had a higher probability of suffering stress than men [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an unprecedented investigation in the state of Bahia, Brazil which was focused on the factors associated with BS in PHC nursing professionals. There are relatively few studies that adopted models that jointly evaluated social, economic, labour and lifestyle factors associated with BS among PHC nursing professionals, although some studies have proposed other conditions of mental illness in the PHC nursing setting [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Además de los síntomas depresivos, Pinhatti et al (2018) observaron que el personal de enfermería de atención hospitalaria tiene una probabilidad en torno a dos veces mayor de sufrir otros desórdenes emocionales como síntomas somáticos y ansiedad. Lua et al (2018) también hallaron una mayor prevalencia de sufrir síntomas como insomnio, fatiga, irritabilidad, olvido, dificultad para concentrarse o problemas somáticos en enfermeras de atención primaria con puntuaciones mayores de uno en ERI (PR = 1,78, IC 0,98-3,23, p = 0,05). Hämmig et al (2012) detectaron valores diversos de burnout o síndrome de estar quemado en el trabajo en función de la profesión.…”
Section: Desequilibrio Esfuerzo-recompensa (Eri) Hipótesis Extrínsecaunclassified